2020
DOI: 10.1097/der.0000000000000715
|View full text |Cite
|
Sign up to set email alerts
|

Financial Burden of Atopic Dermatitis Out-of-Pocket Health Care Expenses in the United States

Abstract: Background: Atopic dermatitis (AD) is associated with considerable financial cost. However, the full burden of out-ofpocket (OOP) expenses is not well understood.Objective: We sought to characterize the OOP health care expenses associated with AD management. Methods: A 25-question voluntary online survey was administered to National Eczema Association members worldwide (n = 113,502). Inclusion criteria (US residents age ≥18 years who either self-reported had AD or were primary caregivers of individuals with AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 35 publications
(62 reference statements)
0
32
1
Order By: Relevance
“…From the perspective of individual households, out-of-pocket (OOP) expenses are an essential and tangible element in routine management of finances. Previous population-based studies showed multifactorial increases in overall OOP expenses in AD patients [ 28 , 29 ], and more recently, it was shown that individuals with AD report a wide variety of distinct medical and non-medical OOP healthcare costs related to AD care [ 30 ]. While black race was shown to be associated with increased healthcare resource utilization in AD [ 26 ], little is known about OOP healthcare expenses related to management of AD care among black individuals.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of individual households, out-of-pocket (OOP) expenses are an essential and tangible element in routine management of finances. Previous population-based studies showed multifactorial increases in overall OOP expenses in AD patients [ 28 , 29 ], and more recently, it was shown that individuals with AD report a wide variety of distinct medical and non-medical OOP healthcare costs related to AD care [ 30 ]. While black race was shown to be associated with increased healthcare resource utilization in AD [ 26 ], little is known about OOP healthcare expenses related to management of AD care among black individuals.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study to assess the direct economic burden for patients with DE, although there have been similar studies surveying related dermatologic conditions such as psoriasis and atopic dermatitis 13‐16 . When directly compared, the cost for DE is notably less than these other conditions (Table 4).…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, this is the first study to assess the direct economic burden for patients with DE, although there have been similar studies surveying related dermatologic conditions such as psoriasis and atopic dermatitis. [13][14][15][16] When directly compared, the cost for DE is notably less than these other conditions ( of the total economic burden of chronic hand eczema revealed average annual total costs between €1311 and €9792, with direct costs between €521 and €3722 each year. 18 Because DE is counted among the different forms of hand/foot eczema, it is likely responsible for a portion of this overall cost.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, out-of-pocket health care expenses associated with AD are a significant burden on patients with AD [ 33 ]. The cost of sophisticated emollient therapies often makes patients hesitant to use the recommended amount of 250 g/week for adults [ 34 ].…”
Section: Overview Of Ad and Treatment Optionsmentioning
confidence: 99%